Mineralization mechanism of organic carbon in maize rhizosphere soil of soft rock and sand mixed soil under different fertilization modes - Guo, Zhen; Han, Jichang; Zhang, Yang; Wang, Huanyuan (Frontiers in Plant Science, 2023)
This article endeavors to investigate the influence of various fertilization methods on the characteristics of rhizosphere soil and organic carbon mineralization in the mixed soil of Mu Us Sandy land under maize cultivation, with the objective of laying the groundwork for low-carbon agriculture and the development of high-quality farmland. The research focuses on soft rock and sand composite soil with a 1:2 ratio, and it comprises four treatments: no fertilization (CK), only chemical fertilization (CF), only cattle manure application (MF), and only oil residue application (DF). The findings revealed that the use of organic fertilizer substantially elevated nutrient content and enzyme activity in the maize rhizosphere soil. Furthermore, it had a notable influence on both soil aggregate diameter and stability. Specifically, the DF treatment led to a significant increase in both soil aggregate diameter and stability. The mineralization rate of organic carbon in the maize rhizosphere soil could be categorized into two distinct phases: a rapid initial decline followed by a slower release. By the end of the incubation period, the cumulative mineralization of organic carbon in the MF, DF, and CF treatments showed a significant increase of 119.87%, 57.57%, and 24.15%, respectively, in comparison to the CK treatment. Additionally, the mineralization rate constants of the DF and MF treatments experienced a substantial rise, with increments of 23.52% and 45.97%, respectively, when contrasted with the CK treatment. The bacterial phyla Actinobacteriota, Proteobacteria, Chloroflexi, Acidobacteriota, and Firmicutes were dominant in the rhizosphere soil bacterial community. Specific genera such as Nocardioides and Sphingomonas showed significant correlations with organic carbon mineralization. The application of different organic fertilizer can improve soil physical, chemical and biological properties, and promote the mineralization process of organic carbon in maize rhizosphere soil. Notably, the DF treatment exhibited the most favorable outcome, improving the overall quality of maize rhizosphere soil while incurring a minimal loss of unit organic carbon. These findings hold significant implications for optimizing field management practices and augmenting soil quality.